Homeless people: a review of personality disorders - Henriques-Calado, Joana; Gama Marques, João (Frontiers in Psychiatry, 2024)
Personality disorders in homeless people pose a challenge to the medical community and society, requiring specialized approaches for these super-difficult patients. The prevalence of personality disorders is higher in homeless populations than in the general population. However, there is a knowledge gap regarding personality disorders among people experiencing homelessness, and the implications of this lack of recognition are substantial. This paper provides a brief narrative review of personality disorders among homeless individuals. The primary importance and specificity of these disorders in this population remain unexplored. We searched PubMed and Web of Science databases in February and November 2023 using the keywords 'homeless' and 'personality disorder', and selected fifty-eight studies to be included in this literature review. The main themes of the results were personality disorders in homeless individuals and comorbid psychiatric disorders; risk factors and other psychological and behavioral data; clinical and intervention outcomes; and challenges linked to assessment, treatment, and intervention. The homeless population experiences significant diagnostic variability and the diagnosis of personality disorders is still evolving, contributing to difficulties in diagnosis, assessment, and treatment. A future challenge is to raise clinical awareness and optimize research knowledge, assessment, and intervention in personality disorders among homeless individuals with comorbid psychiatric disorders.